The Role of Virtual Museums in Restarting Tourism Post- Covid19 - AbuElEnain, EmadEddin Ahmed (Al-Adab Journal, 2022)
Virtual museums are designed as interactive websites in which information is communicated smoothly by allowing the possibility of 3Dvirtual tours in the museum and obtaining information through a database. These websites represent virtual entities in order to display a number of museum holdings that exist in different places with the possibility of commenting on them. Additionally, these museums rely on digital audio and visual technologies created on the Internet with the aim of promoting a museum. It is possible that this museum does not have a real presence on the ground to preserve artifacts like paintings, pottery, and sculptures and the like. The current study explores this new boom (the era of electronics, computers, the international information network, e-mail and other achievements and developments that made it easier for people to obtain high speed and accurate information about any place, from their homes). The use of modern technologies has an important and pivotal role in distinguishing the work of the tourist guide, especially by relying on virtual reality techniques that contribute effectively to simulating the natural reality of tourist attractions. The main aim of this study is to focus on how to improve virtual museums to help people with special needs and qualifying tourist guides in the use of modern technologies, scientific tourism, and educational, academic and artistic museums. These museums contain an integrated virtual electronic guide that contains all the information related to tourist attractions and archaeological sites that could be useful for tourists. The research then investigates potentialities of working to increase the average number of nights of residence, by expanding the base of tourist attractions of all kinds to overcome the problem of seasonality and reducing the prices to encouraging incentive tourism and holding carnival shows to attract tourists to spend more days and nights in the tourism destination. This research first examines relevant literature on possibility to develop virtual museums’ important and pivotal role in spreading the culture of tourism and the development of the tourism processes from the traditional towards the modern style that depends on artificial intelligence techniques. Findings revealed that modern technologies have an important and pivotal role in the development of tourism and facilitate the processes of museums to integrate practical reality with virtual reality. The study provides recommendations that could encourage more tourists to enjoy their visit and improve marketing efforts, to increase the number of visitors of tourist destinations.